Avaliação de germoplasma de meloeiro quanto à tolerância à seca - Matos, Renata Fernandes de (2020)
The melon agribusiness in Brazil has been boosted in the last decades, having as its main support the production of the Semi-Arid region of the Northeast of Brazil, which presents edaphoclimatic similarities with the center of origin of the culture, for which regions of Africa have been pointed out, Middle East and, above all, Asia. In recent years, needs related to climate change have arisen in the productive sector, so that the display of drought-tolerant genotypes has become the focus of many breeding programs. In this sense, this study sought to: I - evaluate the effect of water stress induced by PEG 6000 on melon seeds; II - to characterize melon accessions in terms of tolerance to water stress. The tests were conducted at the Seed Analysis Laboratory of the Federal University of Ceará, in which 34 melon accessions were given from the Melon Active Germplasm Bank (BAG) of Embrapa Hortaliças and the Cucurbitaceae BAG to the Northeast of Brazil, for Banco Melão do Semiárido within the Alelo system, which includes melon accesses and is located at Embrapa Semiárido, in Petrolina-PE. The seeds were submitted to germination on Germitest® paper and kept in a B.O.D. at 25ºC. Water stress was simulated with the use of polyethylene glycol 6000 (PEG 6000), with which the potentials -0,2, -0,4, -0,6, -0,8 and -1,0 Mpa were used, being the potential 0,0 Mpa (absence of stress) only with the use of distilled water. The following characteristics were evaluated: percentage of germination, germination speed index, average germination time, length of the aerial part, length of the root part, fresh mass of the aerial part, fresh mass of the root part, dry mass of the aerial part and dry mass the root part. A completely randomized design was adopted, with four replications of 50 seeds. Statistical analysis was performed using the free computer system SAS. When assessing the accessions in all water potentials, it was identified that: the increase in the intensity of water stress reduced the germination and the establishment of melon seedlings; the water potential -0.8 Mpa proved to be limiting for seed germination, mainly affecting the germination percentage (%G), germination speed index (IVG), average germination time (TMG) and root part length (CPR), standing out as useful for selection of water stress tolerant genotypes. Subsequently, considering the conditions without stress (0,0 Mpa) and with stress (-0,8 Mpa) it was possible to observe that: six groups with different levels of tolerance were formed for the evaluated accessions; the accesses CNPH 16-439, BGMEL 114 and BGMEL 116 stand out as tolerant to water stress; and the accessions CNPH 09-206, CNPH 11-939, CNPH 11-1077, BGMEL 1, BGMEL 6, BGMEL 7, BGMEL 16, BGMEL 46, BGMEL 72 and BGMEL 110 as sensitive. It is concluded that there is ample genetic variability in the melon germplasm evaluated, and complementary investigations should be carried out that include other genotypes and that explore new aspects, such as morphological, physiological, biochemical and agronomic behavior in the face of the stress condition.